The web application hacker's handbook finding and exploiting security flaws - Stuttard, Dafydd 1972-; Pinto, Marcus 1978- (John Wiley & Sons, Inc., 2011)
"Web applications are everywhere, and they're insecure. Banks, retailers, and others have deployed millions of applications that are full of holes, allowing attackers to steal personal data, carry out fraud, and compromise other systems. This innovative book shows you how they do it." "This is hands-on stuff. The authors take a practical approach, showing you the steps involved in finding and exploiting security flaws in web applications. You will learn to: defeat an application's core defense mechanisms and gain unauthorized access, even to the most apparently secure applications; map attack surfaces and recognize potential entry points; break client-side controls implemented within HTML, Java, ActiveX, and Flash; uncover subtle logic flaws that leave applications exposed; use automation to speed up your attacks, with devastating results; and delve into source code and spot common vulnerabilities in language like C#, Java, and PHP." "To defend an application, you must first know its weaknesses. If you design or maintain web applications, this book will arm you with the protective measures you need to prevent all of the attacks described. If you're a developer, it will show you exactly where and how to strengthen your defenses."--Provided by publisher